Relict and modern sediments on the continental shelf of the northern South China Sea: a reconsideration - Wang, Yuming (2023)
Understanding the temporal-spatial patterns of modern and relict sediments is of importance for assessing changes in the Quaternary environment and sea-level. Sedimentological and geochemical data is presented, along with in situ shell-based accelerator mass spectrometry 14C ages of 30 samples from the surface sediments on the northern shelf of the South China Sea (NSSCS). The authors’ data show that the NSSCS surface sediments exhibit considerable diversity in composition. Modern sediments are primarily constrained to the NW inner shelf, which is fed by fluvial sands sourced from Coastal South China river systems and dominated by the Pearl River Estuary delivery. The transport and discharge of the terrestrial sediments to the NSSCS is highly influenced by the Guangdong Longshore Current and its secondary cyclonic eddies. Relict sediments dominated by well-sorted, medium- and coarse-grained sands were identified in the NW Shenhu and NW Dongsha areas of the outer NSSCS. The sedimentology and geochemistry of the relict sediments imply that they were deposited in a dry and cold environment either during the low sea levels of the late Pleistocene (∼40 ka) or the early Holocene (∼10 ka). To the east, the Taiwan Shoal and vicinity are dominated by a sand mixture, at which the relict sediments were reworked by terrigenous supply and modern hydrodynamic environment due to the compound action of the Guangdong Longshore Current, seasonal cyclones, and Kuroshio Intrusion. The present isobaths of ∼−90 m in the NSSCS might be the reflective of the early Holocene coastal delta or the last glacial maximum shoreline.